The effectiveness of e- record system among support staff in UiTM Jengka, Pahang / Afiza Shuib, Siti Norhaslinda Abdullah and Zuraida Hamdany - Shuib, Afiza; Abdullah, Siti Norhaslinda; Hamdany, Zuraida (2011)
The purpose of this study is to recognize the effectiveness of e-record among the support staff at UiTM Jengka, Pahang. There were four (4) research questions; the other factors that contribute to the increase of cost using e-record system, does age play an important factor on the effectiveness of e-record system, does gender play an important factor on the effectiveness of e record system and does the level of education play an important factor on the effectiveness of e record system. The scope of this research is limited to all departments at UiTM Pahang Jengka, only support staff in this UiTM and the organization is situated in UiTM Pahang Campus Jengka. The number of population of this research is 130 and the sample size is 30 support staffs. The sampling technique that was used is simple random sampling. The questionnaire were distributed and successfully returned because the questionnaires were personally collected at the department. Moreover, during the questionnaire are distribute to the respondent, the researchers directly gave them and stay until they finished answer the question. The finding of this research can be concluded as most of the support staffs effectively used e-record system in their department. There are several factors that contribute to the effectiveness using of e-record system among support staff. The effectiveness of e-record system are depends on the frequency uses of the record, less time taken to store, retrieved, maintain and disposed the record. It is recommended that help to improve the record management in departments of UiTM Jengka, Pahang. In addition, it can be use as revision by UiTM Jengka or other company, government or private company in Malaysia to understand the factors that contribute the effectiveness of using e-record system.